On generalized Janowski starlike logharmonic - Mohd, Maisarah Haji; Darus, Maslina; Yavuz Duman, Emel; POLATOĞLU, YAŞAR (My University, 2011)
In this paper, we consider univalent logharmonic mappings of the form f(z) = zh(z)g(z) defined on the open unit disc with the normalization condition g(0) = 1 and h(0) 6= 0. We investigate the class of generalized Janowski starlike defined by subordination. Further we obtain the bound for the functional h(z)/g(z) for f in this class.
Keywords: Logharmonic; univalent; starlike functions; Janowski starlike functions; generalized Janowski starlike functions